The moderating effect of self-efficacy on the relationship between parents and children and academic participation, considering the mediating variable of learning adaptation among secondary school students of Nowshahr city. - meysam karamipour; samaneh mataji; rezvaneh kazem nezhad; maryam esfandyari (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to investigate the moderating effect of self-efficacy on the relationship between parents-children and academic participation, taking into account the mediating variable of learning adaptation among secondary school students of Nowshahr. The current research is applicable in terms of purpose, and descriptive-correlative in terms of nature and method. The statistical population of the current study included parents and students of girls' schools in the first secondary school in Nowshahr, with a number of 2000 students and 2000 parents, of which 384 were selected as a statistical sample using a random cluster method for students, and also 384 were selected by simple random method for parents; based on Cochran's formula. Data collection tools include parent-child relationship questionnaires (Barenzova and Oson, 1982), learning compatibility (Linbin, 2008), self-efficacy (Zhang, 2010), and academic participation (Scafley, 2002). SPSS 26 and Lisrel software were used for analysis. The results showed that there is a significant relationship between parent-child relationships and academic participation of secondary school students in Nowshahr. Also, there is a significant relationship between parent-child and academic participation, taking into account the mediating role of learning adaptation of middle school students in Nowshahr city. Finally, there is no significant relationship between parent-child and academic participation considering the mediating role of learning self-efficacy of Nowshahr secondary school students. Extended abstract Introduction Since the publication of the Family Educational Promotion Law and Co-education in China, the government has encouraged parents to participate in their children's education and help them grow (China, 2021). Studies have shown that communication between parents and children can be an important mechanism to influence their children and help children's growth, health and personality. And it also affects the mental state and behavioral participation of students in learning activities in schools (Liu et al, 2012). Therefore, communication between parents and children can be an effective way to promote learning in school. Academic participation refers to the amount of effort or behavioral participation that students make in the learning process (Peng et al, 2022). In addition, other factors such as learning adaptability can affect students' academic participation. Also, the adaptability of learning can affect students' attitude, participation and effort. (Zhaang et al, 2021) Learning adaptability is defined as a person's ability to maintain a positive attitude. Also, the adaptability of learning has been expressed by taking measures to meet the academic needs of students and adapting to the educational environment. Baker & Siryk (1984) has shown in their studies that learning adaptability can positively predict the student's academic participation. Wang et al, (2020) showed that students with better learning adaptation may be more persistent and focus on their studies without distraction. Therefore, students with strong adaptability can overcome difficulties and devote themselves to learning. On the other hand, self-efficacy is an important contextual factor of learning in the relationship between parents and children, which can be adjusted by individual variables. Research has shown that learning self-efficacy can improve students' academic performance by cultivating mental qualities (Liu, 2017). People with high self-efficacy tend to maintain a good attitude and believe that they can solve learning problems; they are also less likely to experience severe pressure, anxiety or stress (Hong et al, 2021). Therefore, the researcher tries to answer the question: what is the effect of self-efficacy on the relationship between parents-children and academic participation, considering the mediating variable of learning adaptation among secondary school students of Nowshahr city?